2004
DOI: 10.3727/1083542041437558
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of Destination Competitiveness: A Factor Analysis

Abstract: A model is developed to capture the main elements of competitiveness highlighted in the general literature, while appreciating the special issues involved in exploring the notion of destination competitiveness as emphasized by tourism researchers. Associated with the model is a set of indicators that can be used to measure the competitiveness of any given destination. These indicators, comprising both objective and subjective measures, were identified from the major elements comprising the generic destination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
0
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(179 citation statements)
references
References 16 publications
2
164
0
13
Order By: Relevance
“…3;2017 13 destination and tourism services, previous studies might be major source of information. In the study of Cucculelli & Goffi (2015), they found that, the majority of studies look at competitiveness for a single country or a group of countries (e.g., Ahmed & Khron, 1990;Bahar & Kozak, 2007;Dwyer et al, 2003Dwyer et al, , 2004Dwyer et al, , 2012Gomezelj & Mihalic, 2008;Gooroochum & Sugiyarto, 2005;Haahti, 1986;Haahti & Yavas, 1983;Kaynak & Marandu, 2007;Kim & Dwyer, 2003;Kozak & Rimmington, 1999;Lee & Chen, 2010;Mazanec, Wober & Zins, 2007;Miller, Henthorne, & George, 2008;Sirse & Mihalic, 1999;Zhang & Jensen, 2007). Other empirical studies concentrate on islands (Croes, 2010;Mechinda et al, 2010), big cities (Enright & Newton, 2004Minghetti & Montaguti, 2010), particular types of destinations (Botha, Crompton, & Kim, 1999;D'Hautserre, 2000;Lee & King, 2009), famous resort destinations (Kozak, 2002), and regions/provinces (Cracolici & Nijkamp, 2008;Faulkner, Opperman, & Fredline, 1999;Pestana et al, 2011;Zhang et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…3;2017 13 destination and tourism services, previous studies might be major source of information. In the study of Cucculelli & Goffi (2015), they found that, the majority of studies look at competitiveness for a single country or a group of countries (e.g., Ahmed & Khron, 1990;Bahar & Kozak, 2007;Dwyer et al, 2003Dwyer et al, , 2004Dwyer et al, , 2012Gomezelj & Mihalic, 2008;Gooroochum & Sugiyarto, 2005;Haahti, 1986;Haahti & Yavas, 1983;Kaynak & Marandu, 2007;Kim & Dwyer, 2003;Kozak & Rimmington, 1999;Lee & Chen, 2010;Mazanec, Wober & Zins, 2007;Miller, Henthorne, & George, 2008;Sirse & Mihalic, 1999;Zhang & Jensen, 2007). Other empirical studies concentrate on islands (Croes, 2010;Mechinda et al, 2010), big cities (Enright & Newton, 2004Minghetti & Montaguti, 2010), particular types of destinations (Botha, Crompton, & Kim, 1999;D'Hautserre, 2000;Lee & King, 2009), famous resort destinations (Kozak, 2002), and regions/provinces (Cracolici & Nijkamp, 2008;Faulkner, Opperman, & Fredline, 1999;Pestana et al, 2011;Zhang et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Dwyer & Kim (2003) and Dwyer, Mellor, Livaic, Edwards, & Kim (2004) also undertook to contribute to the development of a general model of destination competitiveness. Through a series of development, Dwyer et al (2014) extracted 55 indicators from 135 initial indicators through factor solution analyses using Quartimax rotation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The growing interest in tourism destination competitiveness reflects in the proliferation of the literature on this field (Vila, Darcy & Elisa, 2015). Many of these research projects set out with the objective of identifying the competitiveness of specific destinations, including the United States of America (Ahmed & Krohn 1990), Las Vegas (Chon & Mayer, 1995), European cities (Mazanec, 1995), Southeast Asia (Pearce, 1997), Sun/Lost City in South Africa (Botha, Crompton & Kim, 1999), Southern Australia (Faulkner, Opperman & Fredline, 1999), a United States casino resort (D'Hauteserre, 2000), cultural tourism in Toronto (Carmichael, 2002), Mediterranean resorts (Papatheodorou, 2002), Australia (Dwyer et al, 2004), South Korea and Australia , Spain and Turkey (Kozak 2003), a ski resort in Canada (Hudson, Ritchie & Timur, 2004), Asia-Pacific (Enright & Newton 2005), Slovenia , the Caribbean (ECLAC, 2009), Brazil (Ritchie & Crouch, 2010) and Portugal (Estevão & Ferreira, 2014, Estevão & Ferreira, 2015.…”
Section: Tourism Competitivenessmentioning
confidence: 99%
“…at country or region levels), researchers have developed several different approaches to measure destination competitiveness using a large set of indicators and a wide range of methodologies. Some have used survey data of tourists' perceptions to measure competiveness [2][3][4][5]. Others have used published data (about the economy, environment, infrastructure, etc) to assess and compare the competitiveness of tourist destinations across a range of countries [6].…”
Section: Editorialmentioning
confidence: 99%